Suka suka baking / Muhammad Fizry Adzmir Jamizan - Jamizan, Muhammad Fizry Adzmir (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
The topic of this abstract is redesign. Suka Suka Baking, a vibrant business founded on March 8, 2018, is committed to bringing happiness through its delicious line of baked goods. Our company was founded with a passion for producing unique culinary experiences by Noor Marliah Yahya. Located in Suka Suka Baking, 164 Lorong Kemunting 1/10, 09000 Kulim, Kedah. In the neighborhood, Suka Suka Baking has swiftly grown to be a well-liked brand.The original purpose of creating this product was learning how to create cakes as a hobby. But as the cake takes longer to make, more people want to order the other kinds of cakes that are offered. This product has now developed into a successful industry unto itself and continues to this day. I selected this business because it lacks a corporate identity, a motto, and a representation of the product.We ran across a number of design flaws and issues in our quest for perfection, which put our dedication to providing premium baked goods in jeopardy.Maintaining consistency in the design, creating corporate branding, creating advertising posters, and using social media posed a significant challenge, particu-larly as we increased the scope of our product line. Functionality and vintage funky were two other challenges presented by the packaging design.I used a photo session and added some illustrations to my advertisement as part of the design process. Through the approach I use, I may get customers to learn about this business that sells sweet and delectable cake. We expanded our design concept to include supplementary marketing products like clothing, social media assets, and promotional materials since we recognized the importance of a consistent brand identity. Our goal was to give our audience a seamless and unforgettable brand experience by integrating these technologies with the same visual language seen on our product packaging. In conclusion, Suka Suka Baking has overcome obstacles in the design process and come out stronger and more polishedAs we continue to grow, we will carry forward the lessons learned, ensuring that each bite of a Suka Suka treat is a delightful and memorable experience for our cherished customers.